G721-0282 Exerts Anxiolytic-Like Effects on Chronic Unpredictable Mild Stress in Mice Through Inhibition of Chitinase-3-Like 1-Mediated Neuroinflammation - Ham, Hyeon Joo; Lee, Yong Sun; Lee, Hee Pom; Ham, Young Wan; Yun, Jaesuk; Han, Sang Bae; Hong, Jin Tae (Frontiers in Cellular Neuroscience, 2022)
Chronic stress is thought to be a major contributor to the onset of mental disorders such as anxiety disorders. Several studies have demonstrated a correlation between anxiety state and neuroinflammation, but the detailed mechanism is unclear. Chitinase-3-like 1 (CHI3L1) is expressed in several chronic inflammatorily damaged tissues and is well known to play a major role in mediating inflammatory responses. In the present study, we investigated the anxiolytic-like effect of N-Allyl-2-[(6-butyl-1,3-dimethyl-2,4-dioxo-1,2,3,4-tetrahydropyrido[2,3-d]pyrimidin-5-yl)sulfanyl]acetamide (G721-0282), an inhibitor of CHI3L1, on mice treated with chronic unpredictable mild stress (CUMS), as well as the mechanism of its action. We examined the anxiolytic-like effect of G721-0282 by conducting several behavioral tests with oral administration of G721-0282 to CUMS-treated BALB/c male mice. We found that administration of G721-0282 relieves CUMS-induced anxiety. Anxiolytic-like effects of G721-0282 have been shown to be associated with decreased expressions of CUMS-induced inflammatory proteins and cytokines in the brainhippocampus. The CUMS-elevated levels of CHI3L1 and IGFBP3 were inhibited by treatment with G721-0282 in vivo and in vitro. However, CHI3L1 deficiency abolished the anti-inflammatory effects of G721-0282 in microglial BV-2 cells. These results suggest that G721-0282 could lower CUMS-induced anxiety like behaviors by regulating IGFBP3-mediated neuroinflammation via inhibition of CHI3L1.